Praktikalitas dari Pengembangan E-book Edupark Fisika dengan Pendekatan Saintifik Berdasarkan Destinasi Rumah Gadang - Sadraini, Aini; Hamdi, Hamdi (Jurnal Penelitian Pembelajaran Fisika, 2021)
The development of teaching materials to improve the quality of learning. A developed teaching material must contain provisions for the development of teaching materials. Teaching materials can be integrated with the environment so that physics learning becomes more interesting and challenging. Various kinds of learning resources can be integrated into learning physics, including the environment or educational park (Edupark). Edupark is an educational park to observe the application of physics concepts for students. Edupark is one of the most popular visits by everyone, including students. Meanwhile, the era of the industrial revolution 4.0 had an impact on digital-based education such as non-printed teaching materials in the form of e-books which were integrated with Edupark using a scientific approach. This study uses the Plomp model in Prototyping II and Prototyping III. The data in this study were obtained from the results of student response assessments given in the one-to-one evaluation, small group stage. Besides, it was obtained from the responses of educators and students at the field test stage (prototyping III). The data analysis technique uses a Likert scale. The results of the study concluded that the Edupark physics e-book has a very practical level of practicality, including usable (usable), easy to use, appealing, and cost-effective